Demographic Characteristics and Entrepreneurial Inclination of University Student - Nurhidayah Layoo; Cahyaning Raheni; Sutrisno K. Djawa; Rajindra Rajindra; Rasmi Nur Anggraeni (Universitas Muhammadiyah Palu, 2025)
This study aims to investigate and determine whether there are differences in student entrepreneurship inclination based on demographic factors such as gender, age, work experience, and marital status. The research sample consisted of 356 students who had taken entrepreneurship courses. Data was collected via questionnaires and analyzed using the Mann-Whitney and Kruskal Wallis test methods. The findings revealed that there was no difference in entrepreneurship inclination between male and female students, as well as between various age levels. What is different is the entrepreneurship inclination of students between those who have had work experience and those who have never worked and between married and unmarried students. Students who have worked and married are more likely to be inclinationed in entrepreneurship. This study has implications for the learning methods of entrepreneurship courses and other related courses that need to be redesigned to be more practical than theoretical, assist with capital to start a business and provide entrepreneurial assistance to increase entrepreneurial capacity and teach students responsibility.